The Interpersonal Neurobiology of Intersubjectivity - Schore, Allan N. (Frontiers in Psychology, 2021)
In 1975 Colwyn Trevarthen first presented his groundbreaking explorations of the origins of human intersubjectivity. His influential model dictates that at 2-3 months, during intimate, playful, face-to-face protoconversations the emotions of both the infant and mother are nonverbally communicated, perceived, mutually regulated and expressed in spontaneous, synchronized, reciprocal rhythmic-turn-taking interactions that promote the development of the infant’s brain. In this work I offer an interpersonal neurobiological model of intersubjective protoconversations as bidirectional visual-facial, auditory-prosodic, and tactile-gestural right brain-to-right brain nonverbal communications that facilitate the experience-dependent maturation of the infant’s right brain, which is in an early critical period of growth. I also offer recent brain laterality research on the central role of the right temporoparietal cortex, a central node of the social brain, in intersubjective nonverbal communications, as well as an interpersonal neurobiological model of the development of intersubjective mutual play and mutual love over the first year of life and beyond. In the final section I present recent hyperscanning research that simultaneously measures each member of a dyad during a two-person social interaction that demonstrates the critical role of the right temporoparietal cortex in intersubjective nonverbal communication, and documents a right-lateralized interbrain synchronization between the patient and therapist in the co-constructed therapeutic alliance. Lastly I discuss the relationship between the affect communicating functions of the intersubjective motivational system and the affect regulating functions of the attachment motivational system.